Nursing Analysis in Disorder Patients with Cardiovascular System Approach The Model of the Roy Adaptation Theory - Mutarobin Muatarobin (Poltekkes Kemenkes Semarang, 2020)
Background: The prevalence of patients with an increase in the cardiovascular system is increasing. Nurses are expected to have a contribution in the handling of patients with cardiovascular disorders by implementing and deepening using the Roy Adaptation Model (MAR). The role as care provider was applied to men who were supported 70 years with CAD 3VD EF 52% POST-CABG X3 OFF PUMP.Purpose: The purpose of the study was to discuss the problem of nursing care in patients with cardiovascular system disorders.Methods: This study uses a case study design with nursing care given to one patient with a cardiovascular system, age disagreement and does not specify the sex to be used in a case study. Data analysis techniques by analyzing data from the assessment to evaluation and documentation.Results: The results of the research obtained by policy and stimulus studies can be applied more optimally in the arrangement of ordinary care rooms where patients are stable and not at high risk of reducing cardiac output. Enforcement of attractive nursing diagnoses on NANDA and SDKI. Roy did not arrange specific interventions for each diagnosis based on Roy's Adaptation Model which explained the coping relationships on the regulator and cognator subsystems. Nursing evaluation is completed based on the adaptation achieved by the patient in the mode of adaptation.Conclusion: Roy's Adaptation Model Theory can be used in providing nursing care to patients with cardiovascular system disorders using a format adapted to the format in the hospital.